Implementation of Strengthening Character Education in Physical Education - CARSIWAN CARSIWAN; ACHMAD SANUSI; YOSAL IRIANTARA; DETI ROSTINI (Journal of Physical Education For Secondary Schools, 2021)
Introduction: Character education is intended not only for individual interests but also for the benefit of society and the nation's future. Purpose: This research aims to analyze and describe the implementation of strengthening character education in learning physical education, sports, and health. Methods: This research uses a qualitative approach with a case study method. The research subjects were physical education teachers. Data collection techniques through observation, interviews, and documentation studies. Data analysis with steps: reduction, data presentation or data display, concluding. Results: The teacher implements learning by applying effective communication, coordinating all teaching, and being a leader. Conclusions: The implementation of strengthening character education is integrated with the performance of sports and health physical education learning. The teacher acts as a leader, coordinator, and communicator to move all students according to their respective duties and functions.